Investigation of the interest of medical and wellness services in Hungarian women - Szabó, Katalin (Acta Carolus Robertus, 2022)
Due to its geological features, Hungary has a special tourist attraction. In Hungary, it has many thermal water wells, so it is a real medicinal water. Globally, it ranks 5th, after Japan, Iceland, Italy and France. Complex therapies are now being built to take advantage of these natural resources, thanks to which spa visits are integrated into people’s everyday lives. It offers an excellent opportunity to heal, stay healthy, combine regular exercise and rest. Health tourism is becoming more widespread, but today they are looking not only for medical services, but also for wellness services. Wellness includes active and passive programs that cam be used for preventive, recreational and relaxation purposes. Its development is significantly influenced by the expansion of spa tourism, wellness hotels, various wellness services and spas. In my research, I examine people’s use of health and wellness services and how these are integrated into recreation.